経時的な増大と疼痛増悪を認めた下顎骨類骨骨腫の1例 - 原田, 佳和; 大矢, 亮一; 大津, 聡美; 秋森, 俊行; 平島, 惣一; 宮脇, 昭彦 (日本口腔外科学会雑誌, 2014)
An osteoid osteoma is a benign tumor. Its growth is limited, and the lesion size is generally less than 15 mm. This type of tumor arises most commonly in long bones of the lower limbs. It is extremely rare in the head and neck region, but relatively frequently develops in the cervical spine. Osteoid osteomas account for about 3 % of all bone tumors，and about 1 % of them arise in the jaw. This tumor occurs most frequently at the age of 20-29 years, and men are more frequently affected than women (man:woman ratio, 2-3:1). We report a patient with a mandibular osteoid osteoma. A 28-year-old man visited our department because of haphalgesia in the lingual gingiva of the right mandibular first premolar. In this region, mild redness and a hard bone-like protrusion were observed, and marked haphalgesia was present. Computed tomography (CT) showed a well-delineated radiopaque area (about 2 mm) surrounded by a radiolucent band. After about a year, the swelling in this area increased, and spontaneous pain developed. CT revealed a lesion (about 7 mm in diameter) showing a mixture of radiolucent and radiopaque areas. The tumor was resected under general anesthesia, and an osteoid osteoma was diagnosed on the basis of clinical and histopathological findings. As of 1 year after surgery, there have been no definite findings suggesting recurrence, and we intend to perform further follow-up.